Bali sebagai Wisata Edukasi bagi Wisatawan Anak pada masa Pandemi Covid-19 - Dian Pramita Sugiarti; I Gede Anom Sastrawan; I Made Bayu Ariwangsa; Dea Pratama (JURNAL DESTINASI PARIWISATA, 2021)
Educational tourism becomes a special interest tour for tourists who want to get a learning process whenvisiting a tourist destination. One of them is Bali, during the pandemic tourist destinations in Bali are still indemand by domestic and foreign tourists. Tabanan regency becomes one of the tourist attractions that offereducational tours nagi family tourists and child tourists. The village of cau Coklat, Kampung bIngo and SubakMuseum located in Tabanan Regency offer tourist activities while studying. Tourist activities offered by studyingthe process of harvesting chocolate fruit to making chocolate in the village of cau chocolate, picking organicvegetables and making it into a vegetable salad in the bingo village and seeing the traditional tools of Balinesefarmers in the Subak Museum. The management of educational tourism is inseparable from the importance of thecognitive realm, affective realm and psychomotor realm of children's tourism. This is important due to thepressure that child travelers can under pandemics with closed school conditions, online learning systems andrestrictions on large-scale activities for a long time. so that the management of educational tourism must becarried by all parties in order to be carried out properly and get a good response from child tourists.Keywords : Educational tourism, child tourists,Pandwemi Covid-19